COMUNICACIÓN INTRAFAMILIAR Y SU INFLUENCIA EN EL DESARROLLO CULTURAL EN ESTUDIANTES DE BACHILLERATO GENERAL UNIFICADO DE LA UNIDAD EDUCATIVA “QUEVEDO” AÑO 2022 - Suarez Chichande, Mylena Mayerli (2022)
The present investigative work is born from the purpose of knowing the influence that intrafamily communication has on cultural development in unified general high school students of the "Quevedo" Educational Unit of this year. To determine the stated objective, a survey was elaborated which contained a total of 10 questions, being applied to the students of the aforementioned Educational Unit and thus it was possible to identify the possible reasons that cause the lack of communication within the family nucleus and that they do not allow a good cultural development in young people. To solve the existing problem, new techniques are proposed that help improve intra-family communication and have a better cultural development in young people.